Educational Games as a Teaching Tool in Pharmacy Curriculum - Aburahma, Mona Hassan (Am J Pharm Educ, 2015)
The shift in the pharmacist’s role from simply dispensing medications to effective delivery of pharmaceutical care interventions and drug therapy management has influenced pharmacy education.(1-3) The educational focus has shifted from basic sciences to clinical and integrated courses that require incorporating active-learning strategies to provide pharmacy graduates with higher levels of competencies and specialized skills. As opposed to passive didactic lectures, active-learning strategies address the educational content in an interactive learning environment to develop interpersonal, communication, and problem-solving skills needed by pharmacists to function effectively in their new roles.(4-6) One such strategy is using educational games. The aim of this paper is to review educational games adopted in different pharmacy schools and to aid educators in replicating the successfully implemented games and overcoming deficiencies in educational games. This review also highlights the main pitfalls within this research area.